Fibromyalgia a practical clinical guide - Marcus, Dawn A. (Springer Science+Business Media, LLC, 2011)
Caring for patients with fibromyalgia requires an understanding of the complex nature of this condition. "Fibromyalgia: A Practical Clinical Guide" is a state-of-the-art resource designed to clarify the controversy about fibromyalgia and to provide clinicians with the latest information about its pathogenesis and clinical evaluation, as well as evidence-based guidelines for effective treatment. This comprehensive title includes fully referenced, practical information on this fast-emerging field and provides useful clinical suggestions and practical office tools for effectively managi.